Resilience Contributes to Low Emotional Impact of the COVID-19 Outbreak Among the General Population in Italy - Lenzo, Vittorio; Quattropani, Maria C.; Musetti, Alessandro; Zenesini, Corrado; Freda, Maria Francesca; Lemmo, Daniela; Vegni, Elena; Borghi, Lidia; Plazzi, Giuseppe; Castelnuovo, Gianluca; Cattivelli, Roberto; Saita, Emanuela; et al. (Frontiers in Psychology, 2020)
Background The COVID-19 outbreak is severely affecting overall mental health with unknown psychological consequences. Although a strong psychological impact is possible, few evidences are still available. Past studies have shown that resilience decreases the negative effects of stress. This study aimed to examine depression, anxiety, and stress among the Italian general population during the phase characterized by lockdown, and to investigate the role of resilience as a potential predictor. Methods A total sample of 6314 Italian people participated in this study. Participants were recruited between March 29 and May 4 2020 through an online survey. The Depression Anxiety Stress Scales-21 (DASS-21) and the Resilience Scale (RS) were administered. Demographic data and lockdown related information were also collected. A correlational analysis was carried out to examine relationships between psychopathological domains and resilience. Three hierarchical regression analyses were conducted using the depression, anxiety, and stress as dependent variables and the resilience as independent variable controlling for age, gender, and education. COVID-19 specific variables were also included in the three regression analyses. A further exploratory analysis was carried out to examine which aspects of resilience predict depression, anxiety, and stress. Results The prevalence of moderate to extremely severe symptoms among participants was 32% for depression, 24.4% for anxiety, and 31.7% for stress. The sample mean scores on depression, anxiety, and stress were higher than the normal scores reported in the literature. Results of correlational analysis showed that resilience factors, such as meaningfulness, self-reliance, existential aloneness, and equanimity, are inversely associated with depression, anxiety, and stress. Results of regression analyses indicated that resilience was statically significant in predicting depression, anxiety, and stress. Geographic area of residence and infected acquaintances were also significant predictors. Regarding the resilience factors, results revealed that meaningfulness, perseverance, and equanimity were statistically significant in predicting all the DASS-21 scales. Conclusions About a third of respondents reported moderate to extremely severe depression, anxiety, and stress. The present study suggests that psychological resilience may independently contribute to low emotional distress and psychological ill-being. These findings can help explain the variability of individual responses during the COVID-19 outbreak.